Cognitive Semantic Features of Phraseological Units Denoting Human Intellectual Abilities in English and Uzbek Language - Norboboyevna, Gulchexra Tursunova (Indonesian Journal Publisher, 2024)
The exploration of phraseological units through a cognitive semantic lens has garnered significant attention, revealing insights into how language reflects underlying cognitive structures. This study builds upon existing research by examining English and Uzbek phraseological units related to human intellectual abilities. Drawing on cognitive linguistic theories, including conceptual metaphor and image schemas, the research aims to uncover the cognitive semantic features embedded in these units. A comprehensive analysis reveals that both English and Uzbek phraseological units utilize metaphorical extensions, metonymic representations, image schemas, and conceptual metaphors to convey intellectual concepts. However, cultural and linguistic factors shape the expression of cognitive semantic features. English may employ diverse metaphors spanning different sensory experiences, while Uzbek might focus more on visual and physical metaphors. Cultural nuances influence expressions like